2008
DOI: 10.1590/s0036-36342008000400010
|View full text |Cite
|
Sign up to set email alerts
|

Facilitadores y barreras para el consumo del complemento alimenticio del Programa Oportunidades

Abstract: Results shows the incongruence between the Programs recommendations and the preferences and practices of the target population and provides important elements to be considered in the promotion of the NS .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
0
3
0
3
Order By: Relevance
“…The evaluation, however, did not include knowledge or practices related to child nutrition or health-care seeking for childhood illness (Duarte Gómez et al 2005). A qualitative study specifically aimed at assessing the barriers and facilitators for adequate use of the fortified food in rural areas showed that women knew that the vitamins in the fortified food had a beneficial impact on their children (Escalante-Izeta et al 2008). An important barrier was the belief that foods for young children needed to have a more liquid consistency than recommended for the preparation of the fortified food.…”
Section: Journal Of Development Effectiveness 119mentioning
confidence: 99%
“…The evaluation, however, did not include knowledge or practices related to child nutrition or health-care seeking for childhood illness (Duarte Gómez et al 2005). A qualitative study specifically aimed at assessing the barriers and facilitators for adequate use of the fortified food in rural areas showed that women knew that the vitamins in the fortified food had a beneficial impact on their children (Escalante-Izeta et al 2008). An important barrier was the belief that foods for young children needed to have a more liquid consistency than recommended for the preparation of the fortified food.…”
Section: Journal Of Development Effectiveness 119mentioning
confidence: 99%
“…Otras barreras relacionadas al MNP, como la percepción de que es un medicamento, sabor desagradable, efectos secundarios o la asociación a tierra, no se han reportado en otros estudios de Perú (12)(13)(14) . Por su parte, las barreras referidas a la familia y comunidad, ejercen una gran influencia para la adopción de las recomendaciones de cómo usar el MNP, al respecto, un estudio en Perú y otro en México encontraron resultados similares para el uso de suplementos alimentarios, dando cuenta de la fuerte influencia de la familia y la comunidad (12,25) .…”
Section: Discussionunclassified
“…Sin embargo, un enorme desafío de los programas que incorporan alimentos que no son de consumo habitual, es lograr un adecuado nivel de aceptabilidad y consumo. Diferentes países de la región han incorporado a sus programas mezclas proteicas (Incaparina, Bienestarina, Nutricereal, Mi Sopita) con diferente grado de éxito (27)(28)(29). La mayoría de los programas considera un consumo diario del producto y más de una ración diaria, lo que es muy difícil de lograr.…”
Section: Discussionunclassified